2011
DOI: 10.1186/1478-4491-9-23
|View full text |Cite
|
Sign up to set email alerts
|

Paying health workers for performance in Battagram district, Pakistan

Abstract: BackgroundThere is a growing interest in using pay-for-performance mechanisms in low and middle-income countries in order to improve the performance of health care providers. However, at present there is a dearth of independent evaluations of such approaches which can guide understanding of their potential and risks in differing contexts. This article presents the results of an evaluation of a project managed by an international non-governmental organisation in one district of Pakistan. It aims to contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 2 publications
1
23
0
1
Order By: Relevance
“…Full manuscripts were retrieved for all potentially eligible citations and similarly screened. Additional manuscripts [48][49][50][51][52][53][54][55] were excluded during data extraction if, upon review of the full text of the article, they were evaluated as not meeting inclusion criteria.…”
Section: Screening Proceduresmentioning
confidence: 99%
“…Full manuscripts were retrieved for all potentially eligible citations and similarly screened. Additional manuscripts [48][49][50][51][52][53][54][55] were excluded during data extraction if, upon review of the full text of the article, they were evaluated as not meeting inclusion criteria.…”
Section: Screening Proceduresmentioning
confidence: 99%
“…Similarly, in other countries health workers were frustrated by irregularities in payment (Morgan 2010;Ssengooba et al 2012;Fox et al 2013;Population Council 2013) and the relatively low incentives provided as compared with increased workloads undertaken (Witter et al 2011;Fox et al 2013). Moreover, PBF payments were found to be de-motivating in cases where the distribution was not transparent and perceived to be inequitable (Kalk et al 2010;Witter et al 2011;Fox et al 2013). Finally, in Nepal and Democratic Republic of Congo, bonus payments were found to create conflict among health workers (PowellJackson et al 2008;Huillery and Seban 2013).…”
Section: ; National Population Commission and Icf Macro 2009) Wimentioning
confidence: 99%
“…Based on lessons learnt from other settings (Witter et al 2011;Ssengooba et al 2012), planners and policy makers in Nigeria need to be cognizant about effects of delays in payment and inconsistent design of PBF on health worker motivation and performance. Most health workers were dismayed by the reduction in their bonus amounts due to an unexpected, mid-point change of prices of their services and agitated by delays in payments.…”
Section: Is Pbf As Relevant or Powerful Within The Nigerian Context?mentioning
confidence: 99%
“…Review of all 316 abstracts showed that 53 did not focus on data quality or data use barriers pertaining to RHIS or HMIS. These publications were focused on vertical disease programs, including estimation of malaria incidence; access to malaria rapid diagnostic tests; health systems research; maternal death reviews; and different aspects of malaria, maternal health, uptake of mental health services, and health worker performance …”
Section: Resultsmentioning
confidence: 99%
“…health systems research 12 ; maternal death reviews 13 ; and different aspects of malaria, 14,15 maternal health, 16,17 uptake of mental health services, 18 and health worker performance. 19 The publications described the review, synthesis, analysis, and interpretation of data to answer a research question, but data use was not aligned with decision making. Even though these publications did not explicitly discuss system design barriers, they explained issues related to data integration, data flow, data entry, and data analytics.…”
Section: Publication Focus and Distributionmentioning
confidence: 99%